Size control of InAs quantum dots on 2 degrees-off GaAs (100) substrate by the thickness of GaAs buffer layer - Kim, HJ; Park, YJ; Kim, EK; Kim, TW (ELSEVIER SCIENCE BV, 2001)
We have investigated the dependence of the size distributions of InAs quantum dots grown on 2 degrees -off (1 0 0) GaAs substrate on the thickness of the GaAs buffer layer by metalorganic chemical vapor deposition technique. As the thicknesses of GaAs buffer layers were transformed from 7 to 70 ML, the terrace widths were transformed from 25 to 75 nm by bunching effects of Ga adatoms, It was concluded that not only the thickness of GaAs buffer layer but also the AsH3 partial pressure affected much on the terrace width by which the size of InAs quantum dots was successfully manipulated. The wire-like QDs could also be fabricated by using the size control of the InAs QDs, (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: CHEMICAL-VAPOR-DEPOSITION; BEAM EPITAXY; ISLANDS; LASERS